Fresh Red Cells for Transfusion in Critically Ill Adults: An Economic Evaluation of the Standard Issue Transfusion Versus Fresher Red-Cell Use in Intensive Care (TRANSFUSE) Clinical Trial. Issue 7 (July 2019) - Irving, Adam; Higgins, Alisa; Ady, Bridget; Bellomo, Rinaldo; Cooper, D. James; French, Craig; Gantner, Dashiell; Harris, Anthony; Irving, David O.; Murray, Lynne; Nichol, Alistair; Petrie, Dennis; et al.
Abstract : Objectives: Trials comparing the effects of transfusing RBC units of different storage durations have considered mortality or morbidity as outcomes. We perform the first economic evaluation alongside a full age of blood clinical trial with a large population assessing the impact of RBC storage duration on quality-of-life and costs in critically ill adults. Design: Quality-of-life was measured at 6 months post randomization using the EuroQol 5-dimension 3-level instrument. The economic evaluation considers quality-adjusted life year and cost implications from randomization to 6 months. A generalized linear model was used to estimate incremental costs (2016 U.S. dollars) and quality-adjusted life years, respectively while adjusting for baseline characteristics. Setting: Fifty-nine ICUs in five countries. Patients: Adults with an anticipated ICU stay of at least 24 hours when the decision had been made to transfuse at least one RBC unit. Interventions: Patients were randomized to receive either the freshest or oldest available compatible RBC units (standard practice) in the hospital transfusion service. Measurements and Main Results: EuroQol 5-dimension 3-level utility scores were similar at 6 months—0.65 in the short-term and 0.63 in the long-term storage group (difference, 0.02; 95% CI, –0.00 to 0.04; p = 0.10). There were no significant differences in resource use between the two groups apart from 3.0 fewer hospital readmission days (95% CI, –5.3 to –0.8; p = 0.01) during follow-up in the short-term storage group. There were no significant differences in adjusted total costs or quality-adjusted life years between the short- and long-term storage groups (incremental costs, –2, 358; 95% CI, –5, 586 to 711) and incremental quality-adjusted life years: 0.003 quality-adjusted life years (95% CI, –0.003 to 0.008). Conclusions: Without considering the additional supply cost of implementing a freshest available RBC strategy for critical care patients, there is no evidence to suggest that the policy improves quality-of-life or reduces other costs compared with standard transfusion practice. Abstract : Supplemental Digital Content is available in the text.